Performance on a 200 meter combined test: swim suit compared to full clothing - Laakso, B.; Laakso, B. W. H.; Grimstad, R.; Horneman, E. L.; Nysted, H. P. L.; Stallman, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Most drowning occurs in open water as a result of an unexpected submersion (WHO, 2014). This usually means that the victim is clothed for the activity in which they were engaged before submersion. The added resistance of outer clothing makes it more difficult to swim wearing clothing than when only wearing a swim suit (Laakso, et al, 2018; Stallman et al, 2010). Activity during a cold season would include cold weather clothing, increasing the burden even more. While it is generally accepted that swimming with clothing presents challenges not encountered in swim suit only (Stallman, et al, 2010), too little documentation exists on the real differences. Unfortunately, swimming with clothing, disrobing and dressing again are often neglected in the learning/teaching situation, especially in school swimming programs. Many assume that if one can swim in a swim suit, one can swim in clothing. This is not always the case and novice swimmers are especially at risk. We could argue that for those close to the demarcation between ``Can`` and Cannot`` swim, there are those who ``Can`` in a swim suit, but ``Cannot`` when fully clothed. Generally, at some point in time when higher skill levels are achieved, the differences in swimming without and with clothing are diminished. This is one of many arguments for continuing to seek higher levels of achievement. One can always be ``more safe``. In the past two to three decades, research on the effects of cold water and with it, swimming with clothing has increased considerably (Tipton, 1990, Barwood, 2011). Though this should lead to more attention to this neglected activity, it appears not to have done so. In the past, much attention was directed towards disrobing, thinking that this makes swimming easier if one is forced to swim a considerable distance. More recently the positive effects of retaining clothing, thus reducing body heat loss has been the focus. Both positions are an over simplification of the reality. We argue they are of equal importance and deserve equal attention. We can easily imagine situations where both disrobing and retaining clothing are possible solutions to some given risk situation. When experiencing swimming with clothes for the first time, one may face both psychological and physical challenges. This is an argument for starting early and gently. The experience of swimming with clothes is essential during the learning process. Within the school system explored here, swimming is compulsory, especially in Grade 4 though details are not specified. It is however, now compulsory that part of any swimming teaching program in the schools must be conducted in ``open water``. This logically also leads to the inclusion of swimming with clothing. The increased difficulty of swimming with clothing is often the weakness in one`s skill profile which triggers a drowning episode. Once the emergency has become a fact, outer clothing may be the added burden which leads to drowning. While the added energy cost of swimming with clothing has been evaluated (Stallman, et al, 2010, Tipton, 1990, Barwood, 2011), it remains to apply a pedagogically appropriate measuring tool to the practical experience of swimming with clothing. We have chosen a ``combined test`` consisting of ``a) entry into deep water, b) resurfacing and leveling off, c) swim 100m on the front, d) stop and rest with minimal movement for three (3) minutes - half on the front, half on the back; e) surface dive and retrieve an object, f) roll over, g) turn 1800, h) return to the start swimming on the back, i) exit. This combined test is also the ``Competence Goal`` for all Grade 4 children in the Norwegian school system. Note that the pupils were required to progress on this test continuously and were not allowed to have contact with either the bottom of the pool or the sides.